Handling Of Unsignalized Intersections (Simpang Haji Rais) In South Tangerang City - Heris Cahya Kusuma; Tjahjani, AR Indra; Naibaho, Pio Ranap Tua (Program Studi Teknik Sipil, Fakultas Teknik, Universitas Islam Lamongan, 2025)
The H. Rais intersection in South Tangerang City is an intersection with three arms without traffic signals. Simpang H. Rais is a meeting of three roads, namely Jl. H. Jamat Gg. Rais, Jl. Puspitek Segment 1, and Jl. Puspitek Segment 2. This intersection often experiences long queues due to inadequate intersection capacity so that it is unable to accommodate the volume of vehicles during morning and evening rush hours. The research method used was a direct survey method at the research location to collect traffic data at Simpang H. Rais and the surrounding roads. From the research results, the average length of the queue before handling during peak hours on weekdays is 168.52 m and delays are 35,471 with a level of service (LOS) D, while the average length of the queue before handling during peak hours on holidays is 119 .82 m and a delay of 33.52 with a level of service (LOS) D. In the next 5 years, the performance of Simpang H. Rais before handling will become worse with the result that the average queue length during weekday peak hours is 219.64 m and a delay of 49,137 with an intersection service level (LOS) E, while the average queue length during holiday peak hours is 218.28 m and a delay of 43,635 with an intersection service level (LOS) E. Handling is being carried out at Simpang H. Rais in short-term scenario 1 is by fulfilling road equipment facilities and assigning traffic officers, and in short-term scenario 2 by widening the bend radius to a minimum of 7.8 m and widening the H. Jamat Gg road section. Rais becomes 6 m, while the treatment carried out at Simpang H. Rais in the long term is to change the Puspitek road type to 4/2-T with a width per direction of 6 m.